Pro PHP Refactoring - Trucchia, Francesco; Romei, Jacopo; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2010)
Many businesses and organizations depend on older high-value PHP software that risks abandonment because it is impossible to maintain. The reasons for this may be that the software is not well designed; there is only one developer (the one who created the system) who can develop it because he didn’t use common design patterns and documentation; or the code is procedural, not object-oriented. With this book, you’ll learn to identify problem code and refactor it to create more effective applications using test-driven design.
Finding “Bad Smells” in Code -- to Refactoring -- Principles and Rules -- Test-First Development -- Refactoring Tools -- Structuring Behavior -- Changing Class Responsibilities -- Dealing with Data Rationalization -- Reducing to Essential Conditional Executions -- Simplifying Method Calls -- Simplifying Generalization Relationships -- Legacy Code -- Regression Tests -- Refactoring with Patterns.
Keywords: Computer programming; Software engineering; Web Development; Software Engineering/Programming and Operating Systems